STRATEGI KREATIF IKLAN “KISAH LEGENDA NUSANTARA” DALAM MENUMBUHKAN BRAND AWARENESS INDOESKRIM NUSANTARA - Ikhromi Oktafiandi (Universitas Mercu Buana, 2019)
Creative strategy is a planning carried out to achieve a specific goal to be achieved in an advertising. The problems want to be appointed is the thing that concerned with creative strategy Indoeskrim Nusantara